PEMBINAAN KELOMPOK MINAT ROBOTIK TINGKAT SMA MENGGUNAKAN LEGO SPIKE EDUCATION - Sebastian, Danny; Nugraha, Kristian Adi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2024)
Technological developments and automation require changes in learning materials and methods. One material that receives special attention is robotics. Many schools implement robotics skills as part of the learning curriculum. However, many schools still do not have human resources who can provide robotics learning. Apart from that, during the Covid-19 pandemic, many students experienced a decline in their enthusiasm for learning. To overcome this problem, many schools are trying to implement alternative learning methods, such as using games as a learning tool. This activity tries to solve these two problems by creating alternative learning for high school level robotics interest groups using LEGO Spike Education. Apart from that, the project-based learning method is applied to improve critical thinking and problem solving skills. The training activities were carried out over a period of 6 months with a total of 11 students consisting of 5 class X students and 6 class XI students. Learning outcomes for 1 semester are tested and assessed as extracurricular grades. The obstacle experienced was time constraints.